2019
DOI: 10.30845/jbep.v6n3a1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Eco-Innovation and Business Performance in Mexican SMEs

Abstract: Eco-innovation is a relatively recent construct in the literature of marketing, and is gaining more and more importance among researchers, academics and professionals who consider it as an important construct that generates the companies that have adopted and implemented more and better results business, including a higher level of business performance. However, most of the studies published in the current literature have focused on large international companies, and few studies have focused on the analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In Mexico, the implementation of EI practices has been shown to positively impact the business performance of small and medium-sized enterprises, especially in the manufacturing sector [16]. This assertion is further supported by research conducted in Oaxaca, Mexico, which identified a significant connection between eco-innovation and environmental performance in the hotel industry [17].…”
Section: Introductionmentioning
confidence: 80%
“…In Mexico, the implementation of EI practices has been shown to positively impact the business performance of small and medium-sized enterprises, especially in the manufacturing sector [16]. This assertion is further supported by research conducted in Oaxaca, Mexico, which identified a significant connection between eco-innovation and environmental performance in the hotel industry [17].…”
Section: Introductionmentioning
confidence: 80%